THE CORRELATION BETWEEN STUDENTS’ MOTIVATION AND READING COMPREHENSION - Nyoman Tri Sukma Arsani; Ida Bagus Nyoman Mantra; Anak Agung Putu Arsana (Academic Journal on English Studies (AJOES), 2021)
This research used ex-post facto research with correlational design, which was aimed to figure out whether there is a significant correlation between motivation and reading comprehension of the ninth-grade students of SMPN 2 Mengwi in the academic year 2020/2021. The sample of this study was 60 students taken from the ninth-grade students of SMPN 2 Mengwi that were chosen by random sampling method with a lottery system. The data were collected through administering the researchinstruments which were in the form of a structured questionnaire and narrative text in the form of short answer text. In analyzingthe data, the questionnaires were assessed by Likert’s scale rating, and short answer text was measured by using a scoring rubricadopted from Brown 2004. The collected data were analyzed by using SPSS 22 with means of Pearson Product Moment Correlation Test and T-test. The result of the data showed that the significant value of Pearson product-moment correlation was 0.000 and there was clearly revealed the alternative hypothesis was accepted. In other words, the research finding confirmed that there was a significant correlation between motivation and reading comprehension of the ninth-grade students of SMPN 2 Mengwiin the academic year 2020/2021.